Attitudinal loyalty in the budget hotel industry: what are the important factors? / Dwi Suhartanto and Any Noor - Suhartanto, Dwi; Noor, Any (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2013)
Brand loyalty is an important strategy to maintain competitive advantage in the hotel industry. Despite the notable impact that brand loyalty has on business performance, research appears to be lack of attention on attitudinal loyalty and its determinants. In addition, most studies on loyalty in the hotel industry have been focused on star hotels while research in budget hotel has little attention. There- fore, this study is proposed to gain an understanding of how loyalty determinants affect attitudinal loyalty in the budget hotel industry. This study proposes attitudinal loyalty as a single dimension including cognitive, affective, and conative elements. Further, this study proposes that service quality, perceived value, and customer satisfaction directly and indirectly affect attitudinal loyalty. Three hypotheses were developed to test the relationships between loyalty determinants and attitudinal loyalty. The questionnaire data from 399 customer respondents were collected from budget hotels in Indonesia. Finally, partial least square was used to test the hypotheses. The result of testing the attitudinal loyalty model underlines the importance of service quality and customer satisfaction in forming attitudinal loyalty. Although these three factors are important in determining guest loyalty towards a hotel budget, this study highlight that the effect of service quality on loyalty is indirect through cus- tomer satisfaction. These results contribute to the services marketing theory by providing an empirically based insight into the attitudinal loyalty determinants. Additionally, these findings will assist the budget hotel management to develop and implement competitive strategies.